Relevansi Pemikiran Tafsir Jihad M. Quraish Shihab dalam Tafsir al-Misbah - Cholil, Moh. (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
This article reviews concepts and ideas of M. Quraish Shihab on jihad in his landmark work, Tafsir al-Mishbah. As an interpreter of contemporary Muslim in Indonesia, Shihab interprets Jihad as trials and tribulations for the quality of a person who requires patience and fortitude. Jihad also implies MujÃ¢hidâs ability to mobilize all his power and ability to achieve objectives. However, Shihab did not deny that jihad in some verses means war. Moreover, jihad is a level examination of oneâs faith. For Shihab, jihad not only means war, but also means sincerity, hard work, and determination. He also classifies jihad into three kinds, namely jihad against real enemies, jihad against devils, and jihad against lust contained within each human being. For Quraish Shihab, in the context in Indonesia and in some phenomena in other countries, jihad is allowed if there is persecution and violation of human rights.